Oenin and Quercetin Copigmentation: Highlights From Density Functional Theory - Li, Yunkui; Prejanò, Mario; Toscano, Marirosa; Russo, Nino (Frontiers in Chemistry, 2018)
Making use of anthocyanin copigmentation, it is possible to effectively improve color quality and stability of red wines and other foods. This can be done by selecting strong copigments, but a 1-fold experimental screening usually entails a high cost and a low efficiency. The aim of this work is to show how a theoretical model based on density functional theory can be useful for an accurate and rapid prediction of copigmentation ability of a copigment. The present study, concerning the copigmentation between oenin and quercetin under the framework of implicit solvent, indicates that, in these conditions, the intermolecular hydrogen bonds play an important role in the system stabilization. The dispersion interaction slightly affects the structure, energies and UV-Vis spectral properties of the copigmentation complex.